Integrative taxonomic revision of Uropsilus (Uropsilinae, Talpidae) combining genomic, morphological and geographic evidence - Yi-Xian Li; Quan Li; Wen-Yu Song; Xue-You Li; Kenneth Otieno Onditi; Xiao-Xin Pei; Hong-Jiao Wang; Chang-Kun Fu; Shao-Ying Liu; Zhong-Zheng Chen; Xue-Long Jiang (Molecular Phylogenetics and Evolution, 2026)

Monitoring evapotranspiration to link agricultural water use with crop yield at sub-field scales - Adam P. Schreiner-McGraw; Martha C. Anderson; Kenneth A. Sudduth; Curtis J. Ransom; Jisung G. Chang; Feng Gao (Precision Agriculture, 2026)
Purpose Scientists and producers have pursued precision agriculture to increase yields and limit environmental impacts. Applying precision agriculture concepts has not been straightforward, however, because complex interactions between soil and weather govern crop growth. We hypothesize that evapotranspiration (ET) is a single metric that captures interactions between plant status, soil, topography, and weather and can be used to predict spatial patterns in crop yield. Methods We used remotely sensed estimates of ET to calculate a normalized ET metric describing the ratio of actual to reference ET (f RET ) at a research farm located in the U.S. Corn Belt. Using the resulting 30-m resolution maps of f RET , we estimated the within-field variability in crop water stress and used machine learning techniques to relate f RET , soil, and topographic properties to crop yield. Results We show that total growing season ET is not a strong predictor of yield spatial variability ( r < 0.3), but when used to train a random forest model, f RET estimates are stronger predictors (mean R 2 = 0.6). In fact, f RET alone is better at predicting yield than any other combination of soil, topographic, and hydrologic data tested with machine learning methods. We also show that end of season yield can be predicted with just 9 weeks of f RET data which provides the opportunity to use remotely sensed ET to guide in-season site-specific management decisions. Conclusion This novel combination of earth observations and machine learning algorithms can guide sustainable intensification of agricultural systems within the context of increasing water stress.

Functionalized benzylamines from commercial kraft lignin - Chang Dou; Minliang Yang; Nikhil Kumar; Rolin A. Aguilar; Addison J. Hitt; Griffen Gonzalez; Corinne D. Scown; Kenneth L. Sale; Hemant Choudhary; Aaron M. Socha; Ning Sun (Chemical Engineering Journal, 2026)

Exploring community energy cum Aquavoltaics in Taiwan - Sin Yee Tan; Kenneth Bicol Dy; Ching-Cheng Chang; Shih-Hsun Hsu (Aquaculture, 2025)

Pedotransfer function for predicting deep-soil bulk density and assessing soil organic carbon and nitrogen stocks across land uses in coarse-textured soils - Igor L. Bretas; Jose C.B. Dubeux; Liza Garcia; Luana M.D. Queiroz; Mario A. Lira; Martin Ruiz-Moreno; Cristian T.E. Mendes; Tang Zhou; Chang Zhao; Kevin R. Trumpp; Kenneth T. Oduor (CATENA, 2025)

A 12,000-year dinoflagellate cyst record on the Vancouver Island margin, Canada: tracing past climatic, primary productivity and oceanographic conditions - Zhen Li; Vera Pospelova; Kenneth Neil Mertens; Alice S. Chang; Yongsheng Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

DCR2-targeted ultrasound nanobubbles loaded with verteporfin promote M2 macrophage polarization to overcome doxorubicin resistance in breast cancer - Shuyue Guo; Yanqiu Zhang; Yao Wang; Tiantian Guo; Jialin Zhu; Luchen Chang; Wenwu Ling; Kenneth D. Westover; Zhiwei Zhou; Xi Wei (Chemical Engineering Journal, 2025)

Functional effects of subsidies and stressors on benthic microbial communities along freshwater to marine gradients - Kenneth J. Anderson; John S. Kominoski; Chang Jae Choi; Ulrich Stingl (Ecology, 2024)
Leaf litter in coastal wetlands lays the foundation for carbon storage, and the creation of coastal wetland soils. As climate change alters the biogeochemical conditions and macrophyte composition of coastal wetlands, a better understanding of the interactions between microbial communities, changing chemistry, and leaf litter is required to understand the dynamics of coastal litter breakdown in changing wetlands. Coastal wetlands are dynamic systems with shifting biogeochemical conditions, with both tidal and seasonal redox fluctuations, and marine subsidies to inland habitats. Here, we investigated gene expression associated with various microbial redox pathways to understand how changing conditions are affecting the benthic microbial communities responsible for litter breakdown in coastal wetlands. We performed a reciprocal transplant of leaf litter from four distinct plant species along freshwater‐to‐marine gradients in the Florida Coastal Everglades, tracking changes in environmental and litter biogeochemistry, as well as benthic microbial gene expression associated with varying redox conditions, carbon degradation, and phosphorus acquisition. Early litter breakdown varied primarily by species, with highest breakdown in coastal species, regardless of the site they were at during breakdown, while microbial gene expression showed a strong seasonal relationship between sulfate cycling and salinity, and was not correlated with breakdown rates. The effect of salinity is likely a combination of direct effects, and indirect effects from associated marine subsidies. We found a positive correlation between sulfate uptake and salinity during January with higher freshwater inputs to coastal areas. However, we found a peak of dissimilatory sulfate reduction at intermediate salinity during April when freshwater inputs to coastal sites are lower. The combination of these two results suggests that sulfate acquisition is limiting to microbes when freshwater inputs are high, but that when marine influence increases and sulfate becomes more available, dissimilatory sulfate reduction becomes a key microbial process. As marine influence in coastal wetlands increases with climate change, our study suggests that sulfate dynamics will become increasingly important to microbial communities colonizing decomposing leaf litter.

Nanoplastics enhanced the developmental toxicity of aromatic disinfection byproducts to a marine polychaete at non-feeding early life stage - Yun Yang; Xiangru Zhang; Jiarui Han; Wanxin Li; Xinyi Chang; Yuhe He; Kenneth Mei Yee Leung (Chemosphere, 2024)

Risk assessment of e-waste - Liquid Crystal Monomers re-suspension caused by coastal dredging operations - Chang He; Alessandro Stocchino; Yuhe He; Kenneth Mei Yee Leung; Francesco De Leo; Zhen-Yu Yin; Yin-Fu Jin (Science of The Total Environment, 2024)

Piezocatalytic property of PVDF/Graphene self-assembling piezoelectric membrane for environmental remediation - Tsung-Han Huang; Franz Kenneth C. Espino; Xin-Yuan Tian; Januar Widakdo; Hannah Faye M. Austria; Owen Setiawan; Wei-Song Hung; Kristopher Ray S. Pamintuan; Rhoda B. Leron; Ching-Yuan Chang; Alvin R. Caparanga; Kueir-Rarn Lee; et al. (Chemical Engineering Journal, 2024)

Property rights arrangement and stakeholder networks hindering floating photovoltaics: A case of private open-access ponds in Taiwan - Yi-Chieh Chen; Kenneth Bicol Dy; Ching-Cheng Chang; Shih-Hsun Hsu (Energy Policy, 2024)

The important role of fluid chemistry in the hydrothermal alteration of ordinary chondrites: Insights from halite and sphalerite in the Sidi El Habib 001 (H5) meteorite - Shaofan Che; Kenneth J. Domanik; Yao-Jen Chang; Thomas J. Zega (Earth and Planetary Science Letters, 2023)

Differential bone remodeling mechanism in hindlimb unloaded and hibernating Daurian ground squirrels: a comparison between artificial and natural disuse within the same species - Xuli Gao; Siqi Wang; Siqi Shen; Shuyao Wang; Manjiang Xie; Kenneth B. Storey; Caiyong Yu; Etienne Lefai; Wenqian Song; Hui Chang; Changbin Yang (Journal of Comparative Physiology B, 2023)

Empirical nitrogen and sulfur critical loads of U.S. tree species and their uncertainties with machine learning - Nathan R. Pavlovic; Shih Ying Chang; Jiaoyan Huang; Kenneth Craig; Christopher Clark; Kevin Horn; Charles T. Driscoll (Science of The Total Environment, 2023)

Differential bone metabolism and protein expression in mice fed a high-fat diet versus Daurian ground squirrels following natural pre-hibernation fattening - Xuli Gao; Shenyang Shen; Qiaohua Niu; Weilan Miao; Yuting Han; Ziwei Hao; Ning An; Yingyu Yang; Yu Zhang; Han Zhang; Kenneth B. Storey; Hui Chang (Journal of Zhejiang University-SCIENCE B, 2022)

Spatial Ecology of Atlantic Halibut across the Northwest Atlantic: A Recovering Species in an Era of Climate Change - Nancy L. Shackell; Jonathan A. D. Fisher; Cornelia E. den Heyer; Daniel R. Hennen; Andrew C. Seitz; Arnault Le Bris; Dominique Robert; Michael E. Kersula; Steven X. Cadrin; Richard S. McBride; Christopher H. McGuire; Tony Kess; et al. (Reviews in Fisheries Science & Aquaculture, 2022)

Non-clinical Pharmacology of YTX-7739: a Clinical Stage Stearoyl-CoA Desaturase Inhibitor Being Developed for Parkinson’s Disease - Daniel F. Tardiff; Matthew Lucas; Iwona Wrona; Belle Chang; Chee Yeun Chung; Bertrand Le Bourdonnec; Kenneth J. Rhodes; Robert H. Scannevin (Molecular Neurobiology, 2022)
Summary Stearoyl-CoA desaturase (SCD) is a potential therapeutic target for Parkinson’s and related neurodegenerative diseases. SCD inhibition ameliorates neuronal toxicity caused by aberrant α-synuclein, a lipid-binding protein implicated in Parkinson’s disease. Its inhibition depletes monounsaturated fatty acids, which may modulate α-synuclein conformations and membrane interactions. Herein, we characterize the pharmacokinetic and pharmacodynamic properties of YTX-7739, a clinical-stage SCD inhibitor. Administration of YTX-7739 to rats and monkeys for 15 days caused a dose-dependent increase in YTX-7739 concentrations that were well-tolerated and associated with concentration-dependent reductions in the fatty acid desaturation index (FADI), the ratio of monounsaturated to saturated fatty acids. An approximate 50% maximal reduction in the carbon-16 desaturation index was observed in the brain, with comparable responses in the plasma and skin. A study with a diet supplemented in SCD products indicates that changes in brain C16 desaturation were due to local SCD inhibition, rather than to changes in systemic fatty acids that reach the brain. Assessment of pharmacodynamic response onset and reversibility kinetics indicated that approximately 7 days of dosing were required to achieve maximal responses, which persisted for at least 2 days after cessation of dosing. YTX-7739 thus achieved sufficient concentrations in the brain to inhibit SCD and produce pharmacodynamic responses that were well-tolerated in rats and monkeys. These results provide a framework for evaluating YTX-7739 pharmacology clinically as a disease-modifying therapy to treat synucleinopathies.

A Role for Extracellular Vesicles in SARS-CoV-2 Therapeutics and Prevention - Jatin Machhi; Farah Shahjin; Srijanee Das; Milankumar Patel; Mai Mohamed Abdelmoaty; Jacob D. Cohen; Preet Amol Singh; Ashish Baldi; Neha Bajwa; Raj Kumar; Lalit K. Vora; Tapan A. Patel; et al. (Journal of Neuroimmune Pharmacology, 2021)

Evaluation of machine learning methodology for the prediction of healthcare resource utilization and healthcare costs in patients with critical limb ischemia—is preventive and personalized approach on the horizon? - Jeffrey S. Berger; Lloyd Haskell; Windsor Ting; Fedor Lurie; Shun-Chiao Chang; Luke A. Mueller; Kenneth Elder; Kelly Rich; Concetta Crivera; Jeffrey R. Schein; Veronica Alas (EPMA Journal, 2020)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Functional MRI and delay discounting in patients infected with hepatitis C - Holly McCready; Milky Kohno; Michael Kolessar; Laura Dennis; Daniel Kriz; Hannah Luber; Renee Anderson; Michael Chang; Anna Sasaki; Kenneth Flora; Arthur Vandenbark; Suzanne H. Mitchell; et al. (Journal of NeuroVirology, 2018)

Correction to: A Semi-Physiologically Based Pharmacokinetic Model Describing the Altered Metabolism of Midazolam Due to Inflammation in Mice - Ninad Varkhede; Nita Patel; William Chang; Kenneth Ruterbories; M. Laird Forrest (Pharmaceutical Research, 2018)

A Semi-Physiologically Based Pharmacokinetic Model Describing the Altered Metabolism of Midazolam Due to Inflammation in Mice - Ninad Varkhede; Nita Patel; William Chang; Kenneth Ruterbories; M. Laird Forrest (Pharmaceutical Research, 2018)

Understanding post-earthquake decisions on multi-storey concrete buildings in Christchurch, New Zealand - Frédéric Marquis; Jenna Jihyun Kim; Kenneth J. Elwood; Stephanie E. Chang (Bulletin of Earthquake Engineering, 2017)

A hypomorphic mutation of the gamma-1 adaptin gene (Ap1g1) causes inner ear, retina, thyroid, and testes abnormalities in mice - Kenneth R. Johnson; Leona H. Gagnon; Bo Chang (Mammalian Genome, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Protective effects of higher cognitive reserve for neuropsychological and daily functioning among individuals infected with hepatitis C - Maiko Sakamoto; Steven Paul Woods; Michael Kolessar; Daniel Kriz; J. Renee Anderson; Hannah Olavarria; Anna W. Sasaki; Michael Chang; Kenneth D. Flora; Jennifer M. Loftis; Marilyn Huckans (Journal of NeuroVirology, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

A case–control study of tobacco use and other non-occupational risk factors for lymphoma subtypes defined by t(14; 18) translocations and bcl-2 expression - Cindy M. Chang; Jane C. Schroeder; Andrew F. Olshan; Cherie H. Dunphy; Wen-Yi Huang; Ralph S. Baric; Kathleen Conway; James R. Cerhan; Charles F. Lynch; Nathaniel Rothman; Kenneth P. Cantor; Aaron Blair (Cancer Causes & Control, 2010)

Electricity generation coupled to oxidation of propionate in a microbial fuel cell - Jae Kyung Jang; In Seop Chang; Hwa Yeon Hwang; Yeng Fung Choo; JiYoung Lee; Kyung Suk Cho; Byung Hong Kim; Kenneth H. Nealson (Biotechnology Letters, 2010)

The podosomal-adaptor protein SH3PXD2B is essential for normal postnatal development - Mao Mao; Daniel R. Thedens; Bo Chang; Belinda S. Harris; Qing Yin Zheng; Kenneth R. Johnson; Leah Rae Donahue; Michael G. Anderson (Mammalian Genome, 2009)

A Pooled Analysis of Bladder Cancer Case–Control Studies Evaluating Smoking in Men and Women - Diana Puente; Patricia Hartge; Eberhard Greiser; Kenneth P. Cantor; Will D. King; Carlos A. González; Sylvaine Cordier; Paolo Vineis; Elsebeth Lynge; Jenny Chang-Claude; Stefano Porru; Anastasia Tzonou; et al. (Cancer Causes & Control, 2006)

Cooxidation of naphthalene and other polycyclic aromatic hydrocarbons by the nitrifying bacterium, Nitrosomonas europaea - Soon W. Chang; Michael R. Hyman; Kenneth J. Williamson (Biodegradation, 2002)

Comparison and Clinical Application of Frequency Domain Methods in Analysis of Neonatal Heart Rate Time Series - Kevin L. Chang; Kenneth J. Monahan; M. Pamela Griffin; Douglas Lake; J. Randall Moorman (Annals of Biomedical Engineering, 2001)